Dentistry: how to probe and chart. (2nd March 2019) - Bloor, Claire
Abstract : A thorough examination of the oral cavity, teeth and peridontium under general anaesthetic is essential to enable the veterinary surgeon to make an informed diagnosis and recommend an appropriate, individually-tailored treatment plan to owners for their pets. A conscious examination of the oral cavity can provide clues as to what pathology might be present associated with these tissues; however the existence and more importantly the extent of any pathology cannot be truly discovered until the patient is anaesthetised. This article aims to outline the process of oral cavity and dental assessment under general anaesthetic to facilitate optimal treatment plan creation.